National Defense Psychology: Developing A Foundation for Mental and Character of a Youth Perspective - Erik Saut Hatoguan Hutahaean; Yuarini Wahyu Pertiwi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The youth are the successors of the previous generation's efforts to achieve wealth by safeguarding the nation. Indonesia has recently included national defense in its educational curriculum. Psychology is among the academic disciplines that include national defense courses within their curriculum. However, how it is conceived and carried out often focuses on national security without considering psychological factors. Indeed, a must is using a psychological scientific framework coupled with a youth-centric viewpoint. This study aims to identify the meaning of national defense from a youth psychology perspective. The research used a connotation of meaning analysis methodology, which included examining policy literature and scientific literature and then analyzing them about the semantics of national defense. Safeguarding the nation entails prioritizing security, defense, and welfare. The findings also indicate that resilience, self-actualization, and well-being are crucial dimensions of teenage psychology in safeguarding the nation. The capacity of youth to confront stress, overcome obstacles, and attain a more prosperous future serves as the foundation for ascertaining the psychological significance of patriotism among youth.